2010
DOI: 10.1111/j.1600-051x.2010.01539.x
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative effect of basic fibroblast growth factor on periodontal healing in two‐wall intrabony defects in dogs

Abstract: The candidate bFGF treatment supported periodontal regeneration comparable with that of established benchmarks: EMD and PDGF/beta-TCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 29 publications
3
41
0
Order By: Relevance
“…At eight weeks after implantation in nonhuman primates, the FGF2-gelatin group showed significant regeneration of periodontal tissues in a dose-dependent manner [157]. Shirakata et al demonstrated that treatment with FGF2 induced the promotion of periodontal healing in two-wall intrabony defects in dogs, suggesting that they were a possible candidate for replacement of the established benchmarks enamel matrix derivative or platelet-derived growth factor combined tricalcium phosphate [110]. …”
Section: Tissue-specific Applicationsmentioning
confidence: 99%
“…At eight weeks after implantation in nonhuman primates, the FGF2-gelatin group showed significant regeneration of periodontal tissues in a dose-dependent manner [157]. Shirakata et al demonstrated that treatment with FGF2 induced the promotion of periodontal healing in two-wall intrabony defects in dogs, suggesting that they were a possible candidate for replacement of the established benchmarks enamel matrix derivative or platelet-derived growth factor combined tricalcium phosphate [110]. …”
Section: Tissue-specific Applicationsmentioning
confidence: 99%
“…Conventional open‐flap debridement (OFD) falls short of regenerating tissues destroyed by the disease, and current regenerative procedures offer a limited potential toward attaining a complete periodontal restoration 3 . Various biomaterials 4‐10 based on endogenous regenerative technology (ERT) have been used for periodontal tissue regeneration in addition to autogenous 11,12 and allogenic bone grafts, 13,14 but there is not a single graft material that is considered a gold standard in the treatment of intrabony defects (IBDs).…”
mentioning
confidence: 99%
“…Recently, tissue‐engineering procedures using growth factors have been developed to accelerate periodontal healing and regeneration . Topical application of basic fibroblast growth factor (bFGF) was shown to be a powerful pharmacological tool in periodontal healing .…”
mentioning
confidence: 99%